Pengaruh Tingkat Pendidikan, Kualitas SDM, Informasi dan Sosialisasi terhadap Penyusunan Laporan Keuangan di Kabupaten Kulon Progo - Marhaenna Nareswari Nugrastuti; Teguh Erawati (Jurnal Literasi Akuntansi, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are capable of creating very board employment opportunities. However, MSMEs actors often face obstacles, one of wich is in preparing financial reports. This research has purpose to determine the influence of Education Level, Human Resource Quality, Information and Socialization on the understanding of MSMEs financial statement based on SAK – MSMEs in Kulon Progo regency. The population of this research is MSMEs actors with a sample of 100 MSMEs actors located in Kulon Progo Regency. The data collection method uses a questionnire via Google Form by providing a ramdon sampling technique for the respondents. The result of this research indicated thet the level educatin, human reesource quality, information and socialization have a positive and significant on the understanding of MSMEs financial statement preparation based on SAK – MSMEs.